2020
DOI: 10.1126/scitranslmed.aay4145
|View full text |Cite
|
Sign up to set email alerts
|

PAPPA-mediated adipose tissue remodeling mitigates insulin resistance and protects against gestational diabetes in mice and humans

Abstract: Pregnancy is a physiological state of continuous adaptation to changing maternal and fetal nutritional needs, including a reduction of maternal insulin sensitivity allowing for appropriately enhanced glucose availability to the fetus. However, excessive insulin resistance in conjunction with insufficient insulin secretion results in gestational diabetes mellitus (GDM), greatly increasing the risk for pregnancy complications and predisposing both mothers and offspring to future metabolic disease. Here, we repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 107 publications
1
30
0
Order By: Relevance
“…PAPPA is a metalloprotease secreted by the human placenta that modulates insulin-like growth factor (IGF) bioavailability through proteolysis of IGF-binding proteins (IGFBPs) 2, 4, and 5. There is evidence that low concentrations of PAPPA result in impaired proteolysis of adipose tissue IGFBPs, which are up-regulated in adipose depots during pregnancy [30]. In turn, IGF signaling decreases, impairing pregnancy-induced increases in adipocyte number and size as well as tissue vascularization.…”
Section: Interpretation Of Findings and Comparison With Results Of Previous Studiesmentioning
confidence: 99%
“…PAPPA is a metalloprotease secreted by the human placenta that modulates insulin-like growth factor (IGF) bioavailability through proteolysis of IGF-binding proteins (IGFBPs) 2, 4, and 5. There is evidence that low concentrations of PAPPA result in impaired proteolysis of adipose tissue IGFBPs, which are up-regulated in adipose depots during pregnancy [30]. In turn, IGF signaling decreases, impairing pregnancy-induced increases in adipocyte number and size as well as tissue vascularization.…”
Section: Interpretation Of Findings and Comparison With Results Of Previous Studiesmentioning
confidence: 99%
“…Without treatment, it may lead to preterm birth, fetal death and other pregnancy complications due to poor placentation induced by hyperglycemia. Although GDM is usually preventable and manageable, infants of mothers with GDM are at increased risk for heart disease, obesity or type 2 diabetes (205)(206)(207).…”
Section: Gestational Diabetes Mellitusmentioning
confidence: 99%
“…Maternal body mass index (BMI) has a strong association with the risk of GDM, indicating excessive adipocytes are a potential stressor for placentation ( 213 ). Adiponectin and leptin, mainly produced by the placenta during pregnancy, have a wide range of functions in adipose tissue such as vascularization, adipocyte enlargement and expansion ( 207 ). Exosomes from adipose tissue of GDM patients altered placental glucose metabolism by increasing gene expression of the glycolysis and gluconeogenesis pathways ( 214 ).…”
Section: Exosomes In Pregnancy Complicationsmentioning
confidence: 99%
“…In vitro, recombinant PAPPA has been shown to stimulate human adipose tissue to expand in an IGFBP-5 and IGF-1-dependent manner (Gyrup and Oxvig, 2007). Rojas-Rodriguez et al (Rojas-Rodriguez et al, 2020) reported that insulin resistance is closely associated with endothelial dysfunction (Aziz et al, 2018), and hsa_circ_0010283 is involved in vascular smooth muscle cell dysfunction by regulating the miR-133a-3p/pregnancyassociated plasma protein A (PAPPA) pathway (Feng et al, 2020). PAPPA-deficient mice develop insulin resistance in pregnancy.…”
Section: Circrnas and Insulin Resistancementioning
confidence: 99%